An Islamic Perspective of Business Finance (A Comparative Study with Conventional and Capitalistic Financing) - Syed Mahmood Ali; Yugenghar Akkinapally; Prof. Badiuddin Ahmed (International Journal of Management Studies (IJMS), 2021)
India is big country with the population of 1.210 billion of which about 172 million (14%) are Muslims.We are having the conventional system of banking and finance which is based on only interest. A common practice seen here is anyone who is having any surplus money would be interested in starting the finance business instead of investing in productive projects and developing the economy. In this paper we are trying to provide information about the Islamic beliefs on loans, currency, investment and banking and finance besides how to use the money in the various Islamic investment modules. The emphasizing on important investment modules in Islamic Banking and Finance where by practical application can be done to achieve the objective real growth and development of economy.